PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP PRESTASI KERJA KARYAWAN HOTEL SANTIKA PREMIERE BEACH RESORT - I Nengah Aristana; Dewi Syarifah (Jurnal Ilmiah Hospitality Management, 2012)
Hotel Santika Premiere Beach Resort provided education and training to all employees to improve their performance. Through education and training, it is expected to able to improve the employees’ performance in terms of their quality of service. To analyze the influence of education and training, an analysis on the effectiveness of education and training needed to be conducted. From the analysis, it was found that the percentage of the employees’ performance was 58,4%. The result indicated that aducation and training had an influence on the performance of the employees.